2018
DOI: 10.1016/j.molcel.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Kanglemycin A, an Ansamycin Natural Product that Is Active against Rifampicin-Resistant Mycobacterium tuberculosis

Abstract: SummaryAntibiotic-resistant bacterial pathogens pose an urgent healthcare threat, prompting a demand for new medicines. We report the mode of action of the natural ansamycin antibiotic kanglemycin A (KglA). KglA binds bacterial RNA polymerase at the rifampicin-binding pocket but maintains potency against RNA polymerases containing rifampicin-resistant mutations. KglA has antibiotic activity against rifampicin-resistant Gram-positive bacteria and multidrug-resistant Mycobacterium tuberculosis (MDR-M. tuberculos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 46 publications
(54 reference statements)
2
56
0
Order By: Relevance
“…B) The three-dimensional structure of E . coli RNAP holoenzyme was used to map the rpoB and rpoC mutations [ 67 ]. The two subunits β (red) and β’ (blue) are shown as molecular surface.…”
Section: Resultsmentioning
confidence: 99%
“…B) The three-dimensional structure of E . coli RNAP holoenzyme was used to map the rpoB and rpoC mutations [ 67 ]. The two subunits β (red) and β’ (blue) are shown as molecular surface.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of soil metagenomes also revealed that soil bacteria have evolved great diversity in their rifamycin biosynthetic machinery, suggesting an untapped source of rifamycin congeners [110]. For example, the rifamycin congener kanglemycin A inhibits bacterial RNA polymerases via a mechanism that is distinct from rifampicin and retains potency against rifampicin-resistant mycobacteria [110,111].…”
Section: Screening Of Rifamycin Collectionsmentioning
confidence: 99%
“…The reason for the higher MIC of Gram-negatives is most likely due to a reduced penetration of the rifamycins through the outer membranes of Gram-negatives [258]. The rifamycins remain the first-line treatment of tuberculosis (TB) caused by M. tuberculosis and for treatment of non-tuberculous mycobacterial infections [105,119,244]. Collectively, the rifamycins interact with the bacterial DNA-dependent RNAP whereby transcription is blocked.…”
Section: Rifamycin and Derivativesmentioning
confidence: 99%
“…Based on the crystal structure of the RNAP-promoter complex of Thermus thermophiles with kanglemycin A, it became evident that the sugar (β-O-3,4-O,O -methylene digitoxose) and acid (2,2-dimethyl succinic acid) moieties on the ansa bridge in the molecule increase the binding surface of the antibiotic with the RNAP. Furthermore, the additional interaction of the sugar group of kanglemycin A was hypothesized to limit the frequency of resistance development as this would require two simultaneous mutations in the binding pocket of the RNAP [119,120]. Although kanglemycin A (Table 1) itself has not been introduced to the clinics, its discovery might open up for future structural derivatisation efforts in which the ansa bridge might prove to be a valuable "target" for generating new synthetic ansamycin antibiotics with improved bioactivities.…”
Section: Rifamycin and Derivativesmentioning
confidence: 99%